Mediated youth cultures : the internet, belonging and new cultural configurations - Bennett, Andy, 1963-; Robards, Brady (Basingstoke : Palgrave Macmillan, 2014)
Andy Bennett and Brady Robards bring together thirteen timely essays from across the globe that consider a range of 'mediated youth cultures', covering topics such as how stories about growing up are mediated on Facebook, the phenomenon of dance imitations on YouTube, the circulation of zines online, the resurgence of roller derby on the social web, drinking cultures, Israeli blogs, Korean pop music, and more.
Introduction : youth, cultural practice and media technologies / Andy Bennett (Griffith University) & Brady Robards (University of Tasmania) -- Part 1. Online and offline identities -- Youth identities in a digital age : the anchoring role of friends in young people's approaches to online identity expression / Katie Davis (University of Washington) -- Mediating experiences of "growing up" on Facebook's timeline : privacy, ephemerality and the reflexive project of self / Brady Robards (University of Tasmania) -- Young people and mediated private space / t Part 3. Bodies, spaces and places -- Women, sport and new media technologies : Derby Grrrls online / Adele Pavlidis (Griffith University) & Simone Fullagar (Griffith University) -- r "Activitating" young people in the production of virtual worlds / Liam Berriman (University of Sussex) -- Flash mobs and zombie shuffles : play in the augmented city / Susan Bird (Victoria University).
Includes bibliographical references and index.
Keywords: Internet and youth; Online social networks; Youth -- Social life and customs -- 21st century